PEPtalk: postexposure prophylaxis against varicella in children with cancer. Issue 9 (28th June 2011) - Bate, Jessica; Chisholm, Julia; Heath, Paul T; Breuer, Judith; Skinner, Rod; Manley, Sue; Patel, Soonie; Wheatley, Keith; Ramsay, Mary; Kearns, Pamela R; Hambleton, Sophie
Abstract : Objectives: To describe postexposure prophylaxis (PEP) against varicella zoster virus (VZV) in children being treated for malignancy in the UK and Ireland: the population at risk, frequency of exposure, clinical practice and attitudes among healthcare providers. Design: An observational study in three parts: (1) a retrospective survey of serostatus at diagnosis of malignancy, (2) collation of varicella zoster immune globulin (VZIG) dispensing data over a 3-year period and (3) an online survey of paediatric oncologists' clinical practice and beliefs in relation to VZV disease and its prevention. Setting: UK and Ireland. Participants: Children diagnosed with malignancy in 2009 (serostatus survey) or receiving VZIG between April 2006 and March 2009 (VZIG dispensing study). Paediatric oncologists and haematologists working in tertiary paediatric oncology centres and related shared care units in the UK and Ireland (physician survey). Results: Of 1500 children diagnosed with malignancy each year, at least 24% are VZV seronegative. Few centres make efforts to prevent household exposure by vaccinating VZV-susceptible family members. Exposures to VZV result in the administration of PEP to approximately 250 children with cancer annually: half receive an intramuscular injection of VZIG while the remainder receive a course of oral aciclovir. The choice of PEP is made by doctors. There is no consensus among paediatric oncologists as to which is the better option, reflecting the lack of a secure evidence base. Conclusions: A randomised controlled trial to compare the effectiveness and acceptability of VZIG and aciclovir as PEP against varicella is both desirable and feasible.